Seismic Expression of the Timor-Tanimbar, Eastern Indonesia - Darman, Herman (Berita Sedimentologi, 2012)
The Timor-Tanimbar Trough is an oceanic trough, which is an eastern continuation of the Sunda Trench. It marks the boundary between Indo-Australian Plate's continental shelf and the Timor Plate in the north. The trough is located in the south of Timor Island and is called the Timor Trough with WSW to ENE orientation. Further east, the trough orientation changes to SW-NE and is called Tanimbar Trough.A number of seismic lines across Timor-Tanimbar Trough have recently been published by different authors in several publications. Five of those seismic lines which provided regional geological understanding of the southern part of Banda arc, are discussed in this paper. These seismic lines provide a better geological understanding of the area after Hamilton published regional seismic lines in 1979. In this paper, consistent stratigraphic nomenclature has been applied to these key seismic lines. This will help to understand the regional geological process in chronological order.From west to east, the coverage of the sections published in this article are as follow:Section 1: West part of Timor trough, published by Jones et al (2011);Section 2: East part of Timor trough to Australian Platform, published by Lee and Bawden (2011);Section 3: A regional older section, which provides a regional understanding of the tectonic in the area, is published by Hamilton (1979);Section 4: South of the Tanimbar trough, published by Carter at al. (2003);Section 5: A regional section across the northern part of Tanimbar trough published by Dinkelman et al. (2010), with details which is published by Roberts et al (2011).This article discusses the observations of these seismic lines, but the alternative interpretations are quite limited, for the lack of access to the original data. Seismic-to-well tie is not explained in the source of these seismic sections, and it will not be discussed in this paper.